ulio Cortázar and the Moments of Argentine Experimental Novel (Anclajes, 2024)
This article deals with the possible relations among Julio Cortázar’s experimental literary program, his main novels and some relevant moments in the development of experimental Argentine literature during the 20th Century. First, we emphasize four aspects found in some of Cortázar’s essays written in the decades of 1940 and 1950. In these essays, we highlight his theory of language, his idea of reality, his conception of certain genres such as poetry and particularly of the novel, as the main genre where writers can explore and expand the possibilities of language and its verbal conquest of reality. Second, we propose to examine relations and interactions between the theoretical aspects mentioned above and the process of writing of the main Cortázar’s novels: Los premios (1960), Rayuela (1963), 62/Modelo para armar (1967) and Libro de Manuel (1973). In this section, we consider different characteristics that manifest diverse experimental aspects in each narration. Finally, throughout the essay and in its conclusions, we intend to frame those aspects and qualities of Cortázar’s works within the dynamics of the Argentine literary system of the 20th Century.
Keywords: Cortázar; Language; Novel; Experimentation; Argentine Literature